Low-dose Ultraviolet-A irradiation selectively eliminates nitrite oxidizing bacteria for mainstream nitritation. (December 2020) - Chu, Zhaorui; Huang, Xiaoyu; Su, Yikui; Yu, Huarong; Rong, Hongwei; Wang, Randeng; Zhang, Liqiu
Abstract: Nitritation is currently known as a bottleneck for mainstream nitrite shunt or partial nitritation/anammox (PN/A). Here we propose a new approach to selectively eliminate nitrite oxidizing bacteria (NOB) for mainstream nitritation by low-dose ultraviolet-A (UVA) irradiation. The results showed that mainstream nitritation was rapidly achieved within 10 days with UVA irradiation at the dose of 0.87 μE L −1 s −1, and nitrite accumulation ratio (NO2 − -N/(NO2 − -N + NO3 − -N) ×100%) stabilized over 80%. Microbial community analysis revealed that two typical NOB populations ( Nitrospira and Ca. Nitrotoga ) detected in the control reactor were suppressed efficiently in UVA irradiation reactor, whereas the Nitrosomonas genus of ammonium oxidizing bacteria (AOB) remained at similar level. Intracellular reactive oxygen species (ROS) analysis indicated that NOB-dominant sludge tends to generate more intracellular ROS compared with AOB-dominant sludge in the presence of UVA, leading to the inactivation and elimination of NOB. Additionally, amounts of microalgae found in UVA irradiation reactor could help to suppress NOB by generating ROS during photosynthesis. Briefly, the UVA irradiation approach proposed in this study was shown to be promising in NOB suppression for reliable mainstream nitritation. Graphical abstract: Image 1 Highlights: Low-dose UVA irradiation can selectively eliminate NOB, while no effect on AOB growth. NOB suppression is due to the biocidal effects of intracellular ROS induced by UVA. UVA irradiation can serve as a promising approach for mainstream nitritation.